An initial boundary value problem for the Boussinesq equation in a Trapezoid - Jenaliyev, M.T.; Kassymbekova, A.S.; Yergaliyev, M.G.; Assetov, A.A. (Bulletin of the Karaganda University. Mathematics Series, 2022)
This paper considers an initial boundary value problem for a one-dimensional Boussinesq-type equation in a domain, that is, a trapezoid. Using the methods of the theory of monotone operators, we establish theorems on their unique weak solvability in Sobolev classes.